Modal Sosial dan Strategi Kelangsungan Usaha Sektor Informal Pedagang Kaki Lima pada Era Pandemi COVID-19 - Tri Uswatun Hasanah; Nurhadi Nurhadi; Abdul Rahman (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2020)
This study aims to explain the social capital of street vendors and its contribution to the business continuity strategies during the Covid-19 pandemic. This research used qualitative research and case study approach. The data obtained in this study are qualitative data collected through in-depth interviews, observation and documentation. Intake of informants using purposive sampling technique. The source of data came from street vendors who trade food or drinks using motorbikes, carts and tents, totaling eight informans. Informants have been trading in this micro business sector for at least two years as their main occupation. Data were analyzed using interactive analysis techniques, through three stages of data reduction, data presentation, and drawing conclusions. The results of this study indicate that street vendors build social capital through social relationships with other traders, suppliers, customers, families, parking attendants, local residents, as well as RT and PKK social groups. The Covid-19 pandemic had an impact on drastically decreasing the number of consumers so that it had an effect on sales volume which decreased by 50%. The strategies for maintaining the business continuity of street vendors is related to the continuity of marketing, production and capital. The strategies carried out by street vendors is to strengthen and expand the network of customers, cooperate with other vendors in marketing activities, reduce the amount of production and goods from suppliers, and take advantage of government’s financial aid to help their capital problem